International consensus statement on injury and illness reporting in professional road cycling - Heron, N.; Sarriegui, I.; Jones, N.; Nolan, R. (The Physician and Sportsmedicine, 2021)
Introduction Road cycling is a very common recreational and elite sport. To facilitate consistent reporting of injuries and illness in professional road cycling we want to establish terms, definitions, and methods for injury and illness reporting in elite road cycling epidemiology studies, similar to other sports.